2019
DOI: 10.1021/acs.jced.9b00128
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Formic Acid from Aqueous Solutions onto Anion Exchange Resins: Equilibrium, Kinetic, and Thermodynamic Data

Abstract: Wastewaters containing organic compounds such as acids, ketones, phenols, and amines can cause critical environmental problems depending on their concentration and composition. Efficient and low-cost separation of these components may also bring their reuse in industry while cleaning the aqueous streams. Formic acid (FA) is an important raw material in industry and is widely seen in wastewaters. In this study, two different anion exchangers were compared for the separation of FA from aqueous solutions. Effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 39 publications
4
39
0
Order By: Relevance
“…The mechanism of the adsorption process changes depending on the resin basicity. , With a weak basic resin, the mechanism is mainly based on the adsorption of the undissociated forms of acid on the resin, in addition to ion exchange . On the other hand, with a strong basic one, it becomes an anion-exchange process between the dissociated form of the target acid in the solution and the functional group of the resin . Lewatit VP OC 1065 and Amberlyst A21 are both classified as weak resins having a primary (benzyl amine) and tertiary amine (not explicit in the technical sheet), respectively, as functional groups ().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of the adsorption process changes depending on the resin basicity. , With a weak basic resin, the mechanism is mainly based on the adsorption of the undissociated forms of acid on the resin, in addition to ion exchange . On the other hand, with a strong basic one, it becomes an anion-exchange process between the dissociated form of the target acid in the solution and the functional group of the resin . Lewatit VP OC 1065 and Amberlyst A21 are both classified as weak resins having a primary (benzyl amine) and tertiary amine (not explicit in the technical sheet), respectively, as functional groups ().…”
Section: Resultsmentioning
confidence: 99%
“…9 On the other hand, with a strong basic one, it becomes an anion-exchange process between the dissociated form of the target acid in the solution and the functional group of the resin. 33 Lewatit VP OC 1065 and Amberlyst A21 are both classified as weak resins having a primary (benzyl amine) and tertiary amine (not explicit in the technical sheet), respectively, as functional groups (https:// moodle2.units.it). The pH of the VFA mixture tests was 3.21 ± 0.02, which was lower than the pK a of the VFAs (Table 4).…”
Section: Methodsmentioning
confidence: 99%
“…55 During the experimental concentration range, the adsorption of 5-HMF on the three resins was favorable (0 < R L = 1/1 + K L C 0 < 1, 0 < 1/n < 1). 51,56,57 The regression correlation coefficients of the Freundlich isotherm model were better than those of the Langmuir isotherm model, suggesting that the adsorption of 5-HMF onto the surface of XAD761 resin was heterogeneous. The values of K F were decreased with increasing temperature, indicating the exothermic nature of the adsorption process.…”
Section: Resultsmentioning
confidence: 95%
“…Zeidan and Marti studied the separation of formic acid from aqueous solutions with two weak base anion exchange resins, Amberlite IRA-96 and Lewatit MP-64. The results showed that Lewatit MP-64 was more effective in the range of parameters studied . Medeiros and Soares Forte evaluated the efficacy of hydrotalcites composed of 30, 63, or 70% MgO to remove formic acid and acetic acid from aqueous solution.…”
Section: Introductionmentioning
confidence: 99%